Why decisions fail : avoiding the blunders and traps that lead to debacles - Nutt, Paul C. (Berrett-Koehler Publishers, 2002)
Why decisions fail critiques 15 infamously bad decisions that became public debacles. Including the Firestone tire recall and Quakers failed acquisition of Snapple, the author examines how these mistakes could have been avoided and explains how any organizations decision-making process can be improved to prevent such failures. Paul Nutt began by looking at 400 decisions made by top managers involving such topics as products and services, pricing and markets, personnel policy, technology acquisition, and strategic reorganization. Analyzing how each decision was made, he determined that two out of three decisions were based on failure-prone or questionable tactics. He identifies these key errors and suggests alternatives that have proven successful.